Musyawarah Pembentukan Produk Hukum Pelayanan Kefarmasian melalui Model Partisipasi Masyarakat dan Regulatory Impact Assesment (RIA) dalam Penyelesaian Konflik Perizinan Apotek di Kabupaten Indramayu - Arifin, Jajang; Alam, Kodrat (Jurnal Hukum Positum, 2024)
The absence of regional legal products that regulate the distribution of pharmacies by the ratio of population distribution has resulted in the rampant practice of establishing uneven pharmacies in 31 sub-districts and 317 sub-districts/villages in Indramayu Regency and the emergence of conflicts in pharmacy licensing between professional organizations and business actors in responding to the application for operational permits for pharmacies whose locations are located close to each other or facing each other. The problem is determined to find answers to the form of local wisdom that can be transformed into a model of public involvement in the context of the formation of laws and regulations and standards for the formation of laws and regulations that are a reference in the formation of legal products for pharmaceutical services in Indramayu Regency. The research method used is normative juridical One form of local wisdom that can be transformed into a model of public involvement in the context of the formation of laws and regulations is none other than the way of Deliberation which refers to Law Number 12 of 2011 and the concept of Regulatory Impact Assessment (RIA) which contains Community Participation in a series of Consultation and Communication activities at all levels of the formation of laws and regulations.